TEACHER’S AWARENESS IN DEVELOPING PRAGMATIC COMPETENCE OF EFL LEARNERS - Dasep Suprijadi (STKIP Siliwangi, 2013)
This study intends to portray whether or not the teacher is developing learners’pragmatic competence in the teaching of English at the tenth grade of a seniorhigh school in southern Bandung. This study is descriptive in nature guided bytwo research questions covering: 1) What method is used by the teacher in theteaching of English?, and 2) Does the method indicate the teacher’s awarenessin developing learners’ pragmatic competence? The data for this study werecompiled through classroom observation. The study found out that thelanguage-centered method used by the teacher does not indicate the teacher’sawareness in developing learners’ pragmatic competence, since such a methodonly focuses on linguistic forms or grammatical structures. This method seeksto provide opportunities for learners to practice pre-selected, pre-sequencedlinguistic structure through form-focused exercises in class. This studyconcludes that the teacher’s activities are not aimed at raising students’pragmatic competence or offering opportunities for communicative practice.She does not have any effort to equip her students with the necessary knowledgeto enable them to use the target language appropriately. Thus, the teacher tendsto be unaware of developing learners’ pragmatic competence in the teaching ofEnglish.KEYWORDS: awareness, teaching, pragmatic competence